A retrospective study of caseous Lymphadenitis cases in University Veterinary Hospital, University Putra Malaysia and selected farms around Selangor. - Tan, Eunice Vern Shing; Marimuthu, Murugaiyah (2010)
Caseous Lymphadenitis (CLA) is a disease that commonly affects sheep and goats. It is caused by Corynebacterium pseudotuberculosis. Effects of CLA on the economy are tremendous as it causes loss of production due to carcass condemnation and poor reproductive performance. Due to the chronic character of the CLA disease, retrospective study was chosen to determine the predisposing factors that can influence the occurrence of CLA and the common site of CLA abscess. Records from University Veterinary Hospital, UPM were reviewed and goats with swelling on the head, neck, shoulder, and thigh region were noted. Six predisposing factors were age, gender, breed, management system, source of goats, and purpose of the goats. The exposure odds ratio (EOR) was then calculated determine the strength of association between the predisposing factors with the occurrence of CLA. The results of this study indicated that pure bred goats were found to be 3 times more at risk of having CLA compared to mixed bred goats. The submandibular or parotid lymph node was found to be the most commonly affected lymph nodes (66.7%), followed by the prescapular lymph node (20.8%), and prefemoral lymph node (12.5%).